1994
DOI: 10.1212/wnl.44.12.2289
|View full text |Cite
|
Sign up to set email alerts
|

A reduction in serum glucocorticoids provokes experimental allergic encephalomyelitis

Abstract: Glucocorticoid (GCC) therapy usually inhibits inflammatory diseases, but certain regimens can trigger relapses. Clinical use of steroids is not uniform and in some instances may be dangerous. In the present study, GCCs modified the course of experimental allergic encephalomyelitis (EAE) in Lewis rats, a model of inflammatory CNS disease. Continuous treatment with dexamethasone (DEX) completely blocked EAE. RU 486, a GCC antagonist, counteracted the effects of endogenous GCCs and worsened EAE. Sudden withdrawal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 0 publications
1
21
1
Order By: Relevance
“…For example, Lewis rats with relatively reduced HPA reactivity compared with Fischer rats are more susceptible to autoimmune disease than Fischer rats (8,9). Administration of GC inhibits autoimmune disease in Lewis rats, whereas administration of the GR antagonist RU486 increases the severity of disease in these animals (8,31). In addition, enhanced plasma CORT levels may favor the production of Th2 cytokines over Th1 cytokines (25,32,33), thus reducing the severity of EAE (34).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lewis rats with relatively reduced HPA reactivity compared with Fischer rats are more susceptible to autoimmune disease than Fischer rats (8,9). Administration of GC inhibits autoimmune disease in Lewis rats, whereas administration of the GR antagonist RU486 increases the severity of disease in these animals (8,31). In addition, enhanced plasma CORT levels may favor the production of Th2 cytokines over Th1 cytokines (25,32,33), thus reducing the severity of EAE (34).…”
Section: Discussionmentioning
confidence: 99%
“…GCs can lead to severe relapses (Reder et al, 1994), which can be prevented by slowly reducing GCs instead of a sudden withdrawal. This led to the current treatment protocol used in MS patients that includes an oral taper of methylprednisolone (Beck et al, 1992).…”
Section: Side Effects Of Glucocorticoid Therapymentioning
confidence: 99%
“…This could be circumvented by a combination therapy with erythropoietin where the neurodegenerative effects were reduced (Diem et al, 2005). Moreover, it was observed that the fast withdrawal of GCs can lead to severe relapses (Reder et al, 1994), which can be prevented by slowly reducing GCs instead of a sudden withdrawal. This led to the current treatment protocol used in MS patients that includes an oral taper of methylprednisolone (Beck et al, 1992).…”
mentioning
confidence: 99%
“…Stress-induced elevation of endogenous glucocorticoid protects from EAE. Exogenously administered glucocorticoid hormones, which are known to alleviate human autoimmune diseases, can suppress EAE in mice as well (3)(4)(5), and a similar beneficial response is observed in multiple sclerosis (6,7). In contrast, elimination of glucocorticoid by adrenalectomy or antagonist administration worsens disease (3,8).…”
mentioning
confidence: 92%